Analisis Usaha Perikanan Purse Seine Skala Kecil Tipe Satu dan Dua Kapal Dalam Zona Penangkapan Ikan Terukur di WPP-NRI 714 dan 718, Kepulauan Kei - Simon Marsholl Picaulima; Eko Sri Wiyono; Anna K. Ngamel; Frischilla Pentury; Tatia A. Ngangun (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
Measured fishing policies with different technical characteristics and fishing areas in the measured fishing zone greatly affect the development of small-scale purse seine fishing businesses in the Kei Islands. The purpose of this study was to analyze a small-scale purse seine business operating in a measured fishing zone in the Kei Islands. The research method used in this study is a survey research method, respondent determination techniques based on purposive sampling. The data analysis used is descriptively qualitatively and quantitatively. The results showed that the technical aspects of purse seine vessels type two vessels are larger than type one vessel, purse seine fishing areas for type two vessels are in the measured fishing zones WPP-NRI 714 and 718, while purse seine type one vessel operates in WPP-NRI 714. The economic aspect shows that the highest income from businesses, owners, ABK fishermen and FADs is purse seine type two vessels operating in the measured fishing zone WPP-NRI 714. The financial aspect of purse seine fishing business types one and two vessels operating in the fishing zone WPP-NRI 714 and 718 measured fish are feasible to be developed. Small-scale purse seine fishing business type one and two vessels operating in the measured fishing zone WPP-NRI 714 is more effective and efficient technically, economically and financially. For management purposes, the utilization of fish resources in the restricted fishing zone in WPP-NRI 714 should only be intended for small-scale purse seines types one with a vessel capacity of < 5 GT and operating on fishing lanes 1 and 2, while purse seine type two vessels are in the industrial fishing zone at WPP-NRI 718 on lanes 2 and 3.